(untitled) (The Pakistan Development Review, 2006)
The Local Government Ordinance (LGO), formulated by the National Reconstruction Bureau (NRB) in 2000 and promulgated by provincial governments in August 2001, assigns powers, responsibilities, and service delivery functions to three levels of local governments: district, tehsil, and union. Responsibilities for the delivery of social and human development services, such as primary and basic health, education and social welfare, are delegated to the district level, whereas municipal services, such as water, sanitation and urban services are assigned to the tehsil level. The LGO does not only deal with the delivery of public services in its plan but also stresses the need for fiscal decentralisation, claiming that “Fiscal decentralisation is the heart of any devolution exercise. Without fiscal decentralisation no authority is devolved.”